Enhancement of the spin Hall voltage in a reverse-biased planar p-n junction - Nádvornik, L.; Olejnik, K.; Němec, P.; Novák, V.; Janda, T.; Wunderlich, J.; Trojánek, F.; Jungwirth, T. (American Physical Society, 2016)
We report an experimental demonstration of a local amplification of the spin Hall voltage using an expanding depletion zone at a p-n junction in GaAs/AlGaAs Hall-bar microdevices. It is demonstrated that the depletion zone can be spatially expanded by applying reverse bias by at least 10 μm at low temperature. In the depleted regime, the spin Hall signals reached more than one order of magnitude higher values than in the normal regime at the same electrical current flowing through the microdevice. It is shown that the p-n bias has two distinct effects on the detected spin Hall signal. It controls the local drift field at the Hall cross which is highly nonlinear in the p-n bias due to the shift of the depletion front. Simultaneously, it produces a change in the spin-transport parameters due to the nonlinear change in the carrier density at the Hall cross with the p-n bias.